Nursery raising for livelihood security - Sarolia, D K; Meena, R K (Indian Horticulture, 2019)
The growing commercialization and consumerialistic tendency of society in globalized economy has made impact on traditional areas of nursery and plant propagation. The profitability of technology needs to be demonstrated. In nursery enterprises, high input cost is easily overcome by bulk production and high productivity with low mortality. The economic evaluation of plastic house for the year round grafting shows that a net return of ``39,295 from 75 m2 low-cost polyhouse is obtained within 6 months. Nursery raising not only includes the production and supply of grafts and seedlings but also the strategic marketing efforts in order to reach maximum number of clients. It is of significance especially in perennial horticultural crops which has a long gestation period and effects are known only in later stages. The timely availability of plantlets also circumvents problems arising out of erratic weather condition as witnessed in recent times. The loss during plant multiplication in nursery can be minimized by having hi-tech nursery facilities and resolving the common errors. Thus, nursery sector in coming time will definitely play an important role in employment generation and is a remunerative enterprise in the changing national scenario.